2014
DOI: 10.1093/eurheartj/ehu085
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of evolocumab (AMG 145), a fully human monoclonal antibody to PCSK9, in hyperlipidaemic patients on various background lipid therapies: pooled analysis of 1359 patients in four phase 2 trials

Abstract: In addition to LDL-C reduction, evolocumab, dosed either Q2W or Q4W, demonstrated significant and favourable changes in other atherogenic and anti-atherogenic lipoproteins, and was well tolerated over the 12-week treatment period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 25 publications
3
60
0
1
Order By: Relevance
“…This observation confirms previous investigations that have shown that PCSK9 inhibitors, but not statins, reduce levels of this difficult-to-treat lipoprotein. Our results are also consistent with those recently reported for evolocumab, in which a pooled analysis demonstrated LDL-C reduction and favorable changes in atherogenic and anti-atherogenic lipoproteins across various doses and dosing frequencies [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation confirms previous investigations that have shown that PCSK9 inhibitors, but not statins, reduce levels of this difficult-to-treat lipoprotein. Our results are also consistent with those recently reported for evolocumab, in which a pooled analysis demonstrated LDL-C reduction and favorable changes in atherogenic and anti-atherogenic lipoproteins across various doses and dosing frequencies [15].…”
Section: Discussionsupporting
confidence: 93%
“…ADAs occurred infrequently and did not appear to impact the pharmacokinetics, pharmacodynamics, or safety profile of alirocumab. Although the number of patients in our study sample was small, our findings are consistent with those recently reported for evolocumab [15].…”
Section: Discussionsupporting
confidence: 92%
“…Recent data has demonstrated that Lp(a) can be signifi cantly lowered by 20-40% with ASOs to apoB ( 35 ), monoclonal antibodies to proprotein convertase subtilisin/kexin type 9 (46)(47)(48), and cholesterol ester transfer protein inhibitors ( 49,50 ). However, in patients at or above the 80th percentile, corresponding to ‫ف‬ 50 mg/dl plasma Lp(a) concentrations, much greater reduction than is currently achieved with these indirect therapeutic agents would be required to signifi cantly reduce CVD risk, which is thought to occur at levels which exceed [25][26][27][28][29][30] or OxPL-apoB concentrations, consistent with the independence of lowering of Lp(a) and OxPL-apoB on isoform size ( Fig.…”
Section: Alternative Therapies To Lower Lp(a)mentioning
confidence: 99%
“…Previous studies with evolocumab in patients with heFH on stable lipid-lowering therapy have shown additional reductions in LDL-C of ~60% [15,28,35,36]. In the RUTHERFORD-2 trial [37] study, the relationship between LDL-C response to evolocumab and genotype was also investigated.…”
Section: The Rutherford-2 Trial (The Reduction Of Ldl-c With Pcsk9 Inmentioning
confidence: 99%